2008
DOI: 10.1007/s00467-008-0830-1
|View full text |Cite
|
Sign up to set email alerts
|

MAPK and angiotensin II receptor in kidney of newborn rats from losartan-treated dams

Abstract: Several lines of evidence suggest that angiotensin II (A-II) participates in the postnatal development of the kidney in rats. Many effects of A-II are mediated by mitogen-activated protein kinase (MAPK) pathways. This study investigated the influence that treatment with losartan during lactation has on MAPKs and on A-II receptor types 1 (AT(1)) and 2 (AT(2)) expression in the renal cortices of the offspring of dams exposed to losartan during lactation. In addition, we evaluated the relationship between such ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 42 publications
3
23
0
2
Order By: Relevance
“…Machado et al (39) observed that rats that received losartan during lactation presented albuminuria and alterations in renal structure in adult life that were related to the presence of an inflammatory infiltrate in the renal cortex. We observed that the 30-day-old pups from dams treated with losartan during lactation presented increased AT 2 , p-JNK and p-p38 expression in the kidneys and higher numbers of TUNEL (apoptosis) and PCNA-positive cells in the renal cortex (40). Albuminuria, decreased glomerular filtration rate as well as tubulointerstitial alterations and decreased glomerular area were also found in 30-day-old offspring from losartan-treated dams.…”
Section: Renal Development In Offspring Of Mothers That Received Angimentioning
confidence: 73%
“…Machado et al (39) observed that rats that received losartan during lactation presented albuminuria and alterations in renal structure in adult life that were related to the presence of an inflammatory infiltrate in the renal cortex. We observed that the 30-day-old pups from dams treated with losartan during lactation presented increased AT 2 , p-JNK and p-p38 expression in the kidneys and higher numbers of TUNEL (apoptosis) and PCNA-positive cells in the renal cortex (40). Albuminuria, decreased glomerular filtration rate as well as tubulointerstitial alterations and decreased glomerular area were also found in 30-day-old offspring from losartan-treated dams.…”
Section: Renal Development In Offspring Of Mothers That Received Angimentioning
confidence: 73%
“…The MAPK pathways can be activated by oxidative stress, leading to the inflammation processes, 58 apoptosis and the development of renal lesions in losartan-treated pups. 3 However, the effect of tempol treatment in these animals was limited probably because AII also has several effects that are not mediated by oxidative stress such as the proliferation and differentiation of the tubular, interstitial and vascular cells. 4,5,14,15 It can explain the abnormalities in renal vasculature and tubule interstitial compartment observed in both groups of losartan-treated rats, considering that cell proliferation and differentiation are important events in development.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Clinical and experimental evidence indicates that the renin-angiotensin system (RAS) participates in renal development. [3][4][5][6] All RAS components are expressed early at a high intensity in embryogenesis. 7,8 Angiotensin II (AII) stimulates cultured mesangial cells to produce various extracellular matrix (ECM) components 9 and promotes cell proliferation and differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical and experimental evidence indicates that the renin-angiotensin system participates in renal development [1,2,3,4,5,6,7,8,9,10,11,12]. All components of the renin-angiotensin system are highly expressed early in embryogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of the renin-angiotensin system by administration of angiotensin II antagonists in rats during postnatal development causes abnormalities in renal structure characterized by reduced glomerular volume, tubular dilation, papillary atrophy and interstitial expansion of the renal cortex [1,12,13,14] that lead to a progressive loss of renal function [12]. It was proposed that the structural abnormalities in this experimental model might result in part from developmental disruption of the vascular and tubular compartment of the kidney [14].…”
Section: Introductionmentioning
confidence: 99%